Evaluasi Postur Kerja Operator Pemasangan Fire Brick Berbasis Metode Rapid Upper Limb Assessment dan Work Ergonomic Risk Assessment Di PT ABA - Muhammad Shofiyyullah; Nina Aini Mahbubah (Jurnal Serambi Engineering, 2021)
A service provider is known as a job that profoundly depends on human work. Musculoskeletal disorder is considered a risk in such work. PT. ABA is a contractor service company that provide some services. The fire brick installation is a part of the refractory project, which is carried out continuously at the customer's request. Early results using the Nordic Body Map questionnaire found severe risk, which may lead to wellbeing difficulty.  This study aims to evaluate musculoskeletal disorder risk due to inappropriate posture in fire brick installation activities. Rapid Upper Limb Assessment and Work Ergonomic Risk Assessment are ergonomic risk approaches used in this study. This research found two final scores using RULA and WERA calculation. RULA final score is 44, classified as a medium score. The evaluation results of the RULA method obtained a final score of 7 with an extreme condition. An urgent improvement is a necessity in order to improve posture and work positioning of fire brick installation.